The Effect of Financial Performance, Public Ownership, and Company Age on Volun-tary Disclosure (Case Study on Private Non-Foreign Exchange National Bank Compa-ny Listed in Indonesia Stock Exchange) - Diki Maulana Sidik; Mirza Hedismarlina Yuneline (Jurnal Ilmu Manajemen & Ekonomika, 2022)
This study aims to examine the effect of financial performance (profitability, liquidity, leverage), public ownership, and company age on voluntary disclosure of Private Non-Foreign Exchange National Bank companies either partially or simultaneously. The subject in this study were Private Non-Foreign Ex-change National Bank companies that listed in the Indonesian Stock Exchange and published annual fi-nancial reports for the 2014-2018 period. The number of sample were 6 companies. This study used de-scriptive and verification methods with quantitative approach. The data of this study were secondary data that used annual financial reports of each company. The design of hypothesis testing was classic assump-tion test (normality test, autocorrelation test, multicollinearity test, heteroscedasticity test) and multiple linear regression analysis (coefficient of determination, t test and F test). The results show company age partially has significant effect on voluntary disclosure. While financial performance (profitability, liquidi-ty, leverage) and public ownership partially has no effect on voluntary disclosure. The results proved that the longer the company becomes a public company, it is expected that the company will have more experi-ence on the information needs by the investors and will meet their information needs through voluntary disclosure of the company's annual report. Financial performance (profitability, liquidity, leverage), pub-lic ownership, and company age has a significant effect on voluntary disclosure simultaneously with a co-efficient determination of 24.5%.